Spectroscopic Characteristics of Antibacterial Component of Atung (Parinarium glaberrimum Hassk) Seeds - Murhadi .; Soewarno T S; Betty S.L Jennie; Anton Apriyantono; Sedarnawati Yasni (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
Relative purity assay on antibacterial components (isolates) of “atung” seeds using HPLC system (linier gradient of water-methanol, detection on UV at 280/254 nm) showed that the isolate-9 had the highest purity (94%), followed by isolate-6 (69%), isolate-7 (66%), and isolate-12 (66%) respectively; while the other isolates only had 50% of purity. The UV-Visible spectrophotometer analysis on the isolate-9, showed that the λmax (in methanol) were at 213 and 269 nm. From IR spectrum of the isolate, no more information can be obtained except the presence of C-H stretching. Furthermore, the MS spectrum showed that the fragment ion series of 44 (100%), 57, 69, 83, 97, 115, maybe predicted as aliphatic amine compounds. Key word : Relative purity, methanol, C-H Stretching, fragment ion series, aliphatic amine compounds.